Method for continuously producing water glass and silica-alumina sol by using lithium extraction solid waste
Through the thermochemical coupling activation method of lithium-extraction solid waste and the recycling of nitric acid pressurized by-products, the complex and high-cost problems of lithium-extraction solid waste storage and water glass silicon-aluminum sol preparation are solved, and the process is simple, low-cost and environmentally friendly The production of water glass and silicon aluminum sol has promoted the green transformation of the lithium battery material industry.
Patent Information
- Application Number
- CN202411307147.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
The large amount of lithium-extracted solid waste is stored causing environmental pollution, and the preparation methods for water glass and silicon-aluminum sol are complex and costly.
Thermochemical coupling activation method of solid waste extraction is adopted, combined with anhydrous sodium carbonate calcination, water-immersion and acid-immersion reaction, and the by-products of lithium extraction HNO3, Na2CO3, and NaOH are recycled to achieve continuous production of water glass and silicon-aluminum sol. .
It realizes the preparation of water glass and silicon aluminum sol with simple process, low cost and clean process, reduces the storage of solid waste for lithium extraction, and provides a green transformation path for the lithium battery material industry.
Smart Images

Figure CN119176561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of resource utilization of lithium extraction solid waste, and in particular to a method for continuously producing water glass and silica-alumina sol by utilizing lithium extraction solid waste. Background Art
[0002] Lithium is known as white oil and has irreplaceable and extensive applications in the fields of new energy vehicles, energy storage and all independent mobile devices. By the end of 2023, my country's lithium carbonate production reached about 460,000 tons, a year-on-year increase of 31%. Lithium resources in nature mainly exist in salt lake brine and lithium-containing ores (including spodumene, lithium mica, lithium feldspar, etc.). The Sichuan-Tibet region of my country is divided into the western Sichuan pegmatite-type lithium ore belt and the Qinghai-Tibet Plateau salt lake brine-type lithium ore belt according to their ore deposit types and main distribution areas. At present, the main lithium extraction processes of spodumene ore are acid process, alkaline process, salt roasting process and pressure cooking process. Among them, sulfuric acid roasting is a commonly used method, which has the advantages of low energy consumption, small material flow and high production efficiency, but it also has the problems of low lithium recovery rate, large slag production and low comprehensive utilization rate of auxiliary materials. As a new process for producing lithium carbonate by nitric acid pressure leaching (application number: CN 114854986A, CA115321563A), it can not only improve the comprehensive utilization rate of lithium ore, but also simplify the production process and promote acid-base recycling and regeneration. Whether the sulfuric acid method or the nitric acid method is used to extract lithium from spodumene, a large amount of solid waste (referred to as lithium extraction solid waste) will be generated. According to the solid waste output ratio of 1:7 to 1:8, at least more than 5 million tons of lithium extraction solid waste will be generated per year. This output will also increase year by year with the rapid development of the lithium battery industry. Therefore, in this context, reducing the storage of lithium extraction solid waste and realizing the recycling of lithium extraction byproducts (HNO3, Na2CO3, NaOH) will be of great significance to the green transformation of the lithium battery material industry.
[0003] Water glass is a viscous liquid whose main component is sodium silicate, also known as sodium silicate. Water glass is widely used and is involved in almost every aspect of the national economy. It can generally be used to manufacture various silicate products such as white carbon black, silica gel, zeolite, etc. Water glass is also a basic industrial raw material for construction, textiles, machinery, etc.
[0004] The common method for making industrial water glass is to use an organic silicon source or an inorganic silicon source, which is divided into dry and wet methods. The most commonly used raw material is quartz sand. The Si-O bond energy in quartz sand is high and is connected in a frame-like manner in the form of [SiO4]. It usually requires strong alkali and high-temperature melting treatment or high-temperature and high-pressure dissolution, and its preparation process has high energy consumption. In the dry process, the alkali fusion reaction temperature of quartz sand is as high as 1400℃-1600℃. In the wet process, quartz sand and caustic soda need to be carried out at 150℃ and a pressure of 0.5-0.8MPa. Therefore, the pressure reactor equipment has high requirements and the degree of automation is low. The patent (application number: 202210420760.2) discloses a method for preparing water glass at normal pressure. Using quartz glass as raw material, crush the quartz glass and pass it through a 300-500 mesh sieve; then mix it with NaOH solution and stir for 30-40 minutes to obtain a slurry; stir the slurry at a temperature of 60-80°C for 2-4 hours to obtain a water glass coarse material, which is filtered to obtain a water glass concentrate, which can replace the high temperature and high pressure preparation method. A Chinese invention patent (application number: 202010083215.X) discloses a method for preparing water glass using silicate minerals. The silicate mineral is crushed, ground, and screened to obtain a powder, which is leached and activated with a sulfuric acid solution to obtain a highly active powdered silicon oxide, and finally reacted with an alkaline solution at room temperature and pressure to obtain water glass with different moduli. Although quartz and silicate mineral resources are the most widely distributed minerals on the earth, and my country's mineral resources are relatively abundant, as non-renewable resources, they still face the problem of limited reserves and exhaustibility.
[0005] The patent (application number: 202111201953.0) discloses a method for efficiently preparing water glass using coal gangue. High modulus water glass can be obtained by activating the coal gangue, acid leaching, separating and purifying silicon, and mixing and heating with alkali solution, and the recycling of the by-product potassium fluoride is realized. Zhu Mingyan and others also used the coal gangue fluoride salt sintering method to recover 75.25% of SiO2 in the coal gangue, but fluorosilicate decomposes at high temperature to produce toxic silicon tetrafluoride gas, which is easy to cause secondary pollution to the environment. Patent CN102344148.8 discloses a method for producing high modulus water glass using coal gangue acid leaching residue. The acid leaching residue is subjected to multiple dissolution reactions in caustic soda or alkaline filtrate under normal pressure conditions of 90-95°C to achieve modulus improvement. The realization conditions are environmentally friendly and energy-saving, but due to the filtration, rinsing and other operations involved in the preparation process, the preparation cycle is relatively long. Qiu Jiajun et al. prepared water glass by calcining and activating coal gangue, acid dissolving and aluminum extraction, and caustic soda reaction. However, due to the large amount of aluminum oxide in coal gangue, it will react with sodium hydroxide solution to form sodium aluminate, resulting in water glass containing more impurities. There have been many reports on the preparation of water glass using solid wastes such as coal gangue, rice husk ash, and bamboo leaf ash as raw materials. Using them to replace quartz as a silicon source has the advantages of reducing raw material costs, mild operating conditions, and no need for high temperature and high pressure equipment. However, it involves multiple process links such as alkali melting, acid leaching, separation and purification, and filtration, which also brings problems such as long production cycle, high process energy consumption, and increased process costs.
[0006] Silica sol and alumina sol are colloidal solutions of silica particles and alumina particles dispersed in water. Silica-alumina sols with strong and tough skeleton structures and high temperature resistance can be prepared by using different silicon and aluminum sources.
[0007] Chen Gen used aluminum 2-butoxide and tetraethyl orthosilicate as raw materials to prepare silica-alumina sol; Guo Xingzhong et al. dissolved aluminum chloride hexahydrate in dilute hydrochloric acid and added methyl orthosilicate to obtain silica-alumina sol; the patent (application number: 201910425161.8) used amorphous aluminum hydroxide synthesized from inorganic aluminum salts and alkali solution as the aluminum source, added formic acid and acetic acid to prepare aluminum sol, mixed the aluminum sol with the newly prepared acidic silica sol, and obtained spinnable silica-alumina sol after concentration and aging. The sol-gel method for preparing silica-alumina sol is not uncommon, but they all use alkane raw materials such as siloxane and alkanes. As chemical materials, they are not only expensive, but may also have an impact on the environment; in addition, they are all obtained by a two-step mixing method of aluminum sol and silica sol.
[0008] Therefore, it is of great significance to develop a method for preparing water glass and silica-alumina sol with simple process, low cost and green process. Summary of the invention
[0009] The purpose of the present invention is to solve the problem of environmental pollution caused by the large-scale storage of lithium extraction solid waste, and the complex and high-cost preparation methods of water glass and silica-alumina sol, and provide a method for continuously producing water glass and silica-alumina sol using lithium extraction solid waste. The present invention recycles the byproducts HNO3, Na2CO3, and NaOH of lithium extraction by pressurized nitric acid, and realizes the continuous production of water glass and silica-alumina sol during the utilization process, thus opening up new raw material resources for the production of water glass and silica-alumina sol, and also provides technical guarantee for the comprehensive utilization of lithium extraction solid waste.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: a method for continuously producing water glass and silica-alumina sol using lithium extraction solid waste, comprising the following steps:
[0011] S1. Thermochemical coupling activation of solid waste from lithium extraction
[0012] After the lithium-extracted solid waste is ball-milled and mixed with anhydrous sodium carbonate, it is calcined at 650°C to 850°C for 1h to 5h for calcination activation treatment to obtain a calcined product; the chemical reaction is as follows:
[0013] NaAlSi3O8+2Na2CO3=NaAlSiO4+2Na2SiO3+2CO2
[0014] SiO2+Na2CO3=Na2SiO3+CO2
[0015] S2, calcined product soaking
[0016] The calcined product in S1 is placed in deionized water for leaching at normal pressure, with a mass ratio of water to the calcined product being 5:1-20:1, and leaching solution I is obtained by filtering, which is a water glass solution with extremely low Al impurity content; the calcined product and the leaching solution I are subjected to normal pressure leaching for multiple times according to a liquid-to-solid ratio of 5:1-20:1, and a high-solid content water glass solution and a water leaching filter cake are obtained after filtering;
[0017] S3, water leaching filter cake acid leaching
[0018] The water leaching filter cake obtained in S2 is dried, then mixed and stirred with nitric acid, leached, and filtered to obtain leachate II and acid leaching filter cake; the chemical reaction is as follows:
[0019] Na2SiO3+2HNO3=2NaNO3+H2SiO3
[0020] NaAlSiO4+4HNO3=NaNO3+H4SiO4+Al(NO3)3
[0021] H4SiO4→H2SiO3+H2O
[0022] The leachate II is passed through a cationic resin to obtain a silica-alumina sol solution.
[0023] Preferably, the mass ratio of anhydrous sodium carbonate to lithium extraction solid waste in S1 is 0.5-1.5; the lithium extraction solid waste is lithium extraction solid waste with SiO2≧78%, Al2O3≦15%, and a crystal phase composition of feldspar and quartz.
[0024] Preferably, the temperature of the atmospheric pressure leaching in S2 is 20-95°C, and the leaching time is 30-200 min.
[0025] Preferably, the concentration of nitric acid in S3 is 1-6 mol / L, the ratio of nitric acid solution to water leaching filter cake is 5-30 ml / g, and the leaching time is 30-200 min.
[0026] More preferably, in S3, the acid leached filter cake is mixed with sodium hydroxide and the water glass solution obtained in S2 to obtain an alkali-activated low-carbon cementitious material with excellent mechanical properties.
[0027] The beneficial effects of the present invention are:
[0028] 1. The thermochemical coupled activation reaction in the present invention sets the mass ratio according to the ternary phase diagram, thereby ensuring the best activation effect of albite and quartz in lithium extraction solid waste.
[0029] 2. The present invention recycles sodium carbonate, HNO3, a byproduct of lithium extraction, and solid waste from lithium extraction to continuously produce water glass and silica-alumina sol, which has the advantages of simple process, low cost, and clean process, and is easy to realize large-scale production.
[0030] 3. The present invention can conveniently adjust the solid content of water glass by the number of water immersions; and the leachate I only needs to be filtered to prepare the water glass without washing, and the production efficiency is high; at the same time, the leachate II is passed through a cation exchange resin to obtain a silica-alumina sol in one step, without the need to use alkane raw materials such as siloxane and alane, so the cost is low and it is easy to industrialize production.
[0031] 4. In the present invention, the filter residue is an amorphous phase with certain chemical reactivity, and can be directly used to produce alkali-activated gelling materials, and used for the development of unburned ceramsite, pavement materials, and rapid repair materials. Therefore, the present invention can solve the full quantitative utilization of lithium extraction solid waste and realize the slag-free production of lithium carbonate factories by leaching spodumene nitric acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the process flow of the present invention.
[0033] Figure 2 This is the XRD diffraction intensity spectrum of the lithium-extracted solid waste used in the present invention.
[0034] Figure 3 The XRD diffraction intensity spectrum of the calcined product obtained in Example 1 is shown in FIG.
[0035] Figure 4 This is the XRD diffraction intensity spectrum of the water-soaked filter cake obtained by filtration in Example 1.
[0036] Figure 5 This is the XRD diffraction intensity spectrum of the acid leaching filter cake obtained by filtration in Example 1.
[0037] Figure 6 These are sample pictures of the water glass obtained by water immersion in Example 1 and the silica-alumina sol obtained by acid immersion. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0039] Example 1
[0040] Lithium extraction solid waste with SiO2 and Al2O3 mass fractions of 79.79% and 14.44% respectively was taken as raw material.
[0041] 1. Thermochemical coupling activation
[0042] The mass ratio of lithium extraction solid waste to anhydrous sodium carbonate was set to 10:8. 3 g of lithium extraction solid waste was taken, mixed with anhydrous sodium carbonate, ball-milled, and then placed in a muffle furnace for roasting. The roasting temperature of the muffle furnace was controlled to be 750°C, and the reaction was performed for 1.5 hours to obtain activated lithium extraction solid waste. At this time, the phase composition of the activated lithium extraction solid waste was sodium silicate and nepheline phase, and there was still a small amount of quartz phase that was not fully activated.
[0043] 2. Water immersion reaction
[0044] The activated lithium extraction solid waste and deionized water were reacted in a water bath at 60°C for 2h at a liquid-solid ratio of 10ml / g, and filtered while hot to obtain filtrate I, i.e., water glass, in which the silicon dioxide content was 35.44%. The activated lithium extraction solid waste and filtrate I were leached multiple times, and after repeating 3 times, the solid content in the water glass reached 11.23%, and the colloidal particle size distribution was 500-3000nm, showing a unimodal distribution.
[0045] 3. Acid leaching reaction
[0046] The water leaching filter cake is leached with 3 mol / L nitric acid solution at a liquid-solid ratio of 10 ml / g, and the reaction is carried out for 1 hour to obtain leachate II and acid leaching filter cake. The leachate II is passed through a cation exchange resin to obtain a silica-alumina sol with a double peak distribution of colloidal particle sizes of 10-60 nm and 60-600 nm.
[0047] Example 2
[0048] Lithium extraction solid waste with SiO2 and Al2O3 mass fractions of 79.79% and 14.44% respectively was taken as raw material.
[0049] 1. Thermochemical coupling activation
[0050] The mass ratio of lithium extraction solid waste to anhydrous sodium carbonate was set to 10:10, 3 g of lithium extraction solid waste was taken, mixed with anhydrous sodium carbonate, ball-milled, and then placed in a muffle furnace for roasting, and the roasting temperature of the muffle furnace was controlled to be 800°C, and the reaction was carried out for 3 hours to obtain activated lithium extraction solid waste. At this time, the phase composition of the activated lithium extraction solid waste is sodium silicate and nepheline phase.
[0051] 2. Water immersion reaction
[0052] The activated lithium extraction solid waste and deionized water were reacted in a water bath at 60°C for 2h at a liquid-solid ratio of 10ml / g, and filtered while hot to obtain filtrate I, i.e., water glass, in which the silicon dioxide content was 40.58%. The activated lithium extraction solid waste and filtrate I were leached multiple times, and after repeating 3 times, the solid content in the water glass reached 14.88%, and the colloidal particle size distribution was 500-3000nm, showing a single peak distribution.
[0053] 3. Acid leaching reaction
[0054] The water leaching filter cake is leached with 3 mol / L nitric acid solution at a liquid-solid ratio of 10 ml / g, and the reaction is carried out for 1 hour to obtain leachate II and acid leaching filter cake. The leachate II is passed through a cation exchange resin to obtain a silica-alumina sol with a colloidal particle size range of 10-60 nm and 60-600 nm.
[0055] Example 3
[0056] Lithium extraction solid waste with SiO2 and Al2O3 mass fractions of 79.79% and 14.44% respectively was taken as raw material.
[0057] 1. Thermochemical coupling activation
[0058] The mass ratio of lithium extraction solid waste to anhydrous sodium carbonate was set to 10:8. 3 g of lithium extraction solid waste was taken, mixed with anhydrous sodium carbonate, ball-milled, and then placed in a muffle furnace for roasting. The roasting temperature of the muffle furnace was controlled to be 750°C, and the reaction was performed for 1.5 hours to obtain activated lithium extraction solid waste. At this time, the phase composition of the activated lithium extraction solid waste was sodium silicate and nepheline phase, and there was still a small amount of quartz phase that was not fully activated.
[0059] 2. Water immersion reaction
[0060] The activated lithium extraction solid waste and deionized water were reacted in a water bath at 80°C for 3 hours at a liquid-solid ratio of 15 ml / g, and filtered while hot to obtain filtrate I, i.e., water glass, in which the silicon dioxide content was 36.98%. The activated lithium extraction solid waste and filtrate I were leached multiple times, and after repeating 3 times, the solid content in the water glass reached 12.87%, and the colloidal particle size distribution was 500-3000 nm, showing a unimodal distribution.
[0061] 3. Acid leaching reaction
[0062] The water leaching filter cake is leached with 3 mol / L nitric acid solution at a liquid-solid ratio of 10 ml / g, and the reaction is carried out for 1 hour to obtain leachate II and acid leaching filter cake. The leachate II is passed through a cation exchange resin to obtain a silica-alumina sol with a colloidal particle size range of 10-60 nm and 60-600 nm.
[0063] Example 4
[0064] Lithium extraction solid waste with SiO2 and Al2O3 mass fractions of 79.79% and 14.44% respectively was taken as raw material.
[0065] 1. Thermochemical coupling activation
[0066] The mass ratio of lithium extraction solid waste to anhydrous sodium carbonate was set to 10:8. 3 g of lithium extraction solid waste was taken, mixed with anhydrous sodium carbonate, ball-milled, and then placed in a muffle furnace for roasting. The roasting temperature of the muffle furnace was controlled to be 750°C, and the reaction was performed for 1.5 hours to obtain activated lithium extraction solid waste. At this time, the phase composition of the activated lithium extraction solid waste was sodium silicate and nepheline phase, and there was still a small amount of quartz phase that was not fully activated.
[0067] 2. Water immersion reaction
[0068] The activated lithium extraction solid waste and deionized water were reacted in a water bath at 60°C for 2h at a liquid-solid ratio of 10ml / g, and filtered while hot to obtain filtrate I, i.e., water glass, in which the silicon dioxide content was 35.44%. The activated lithium extraction solid waste and filtrate I were leached multiple times, and after repeating 3 times, the solid content in the water glass reached 11.23%, and the colloidal particle size distribution was 500-3000nm, showing a unimodal distribution.
[0069] 3. Acid leaching reaction
[0070] The water leaching filter cake is leached with 5 mol / L nitric acid solution at a liquid-solid ratio of 20 ml / g, and the reaction is carried out for 2 hours to obtain leachate II and acid leaching filter cake. The leachate II is passed through a cation exchange resin to obtain a silica-alumina sol with a colloidal particle size range of 10 to 50 nm and 50 to 500 nm.
[0071] The specification and drawings of the present invention are considered to be illustrative rather than restrictive. On the basis of the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features according to the disclosed technical content without creative labor, all of which are within the protection scope of the present invention.
Claims
1. A method for continuously producing water glass and silica-alumina sol using lithium extraction solid waste, characterized in that: The following steps are involved: S1. Thermochemical coupling activation of solid waste from lithium extraction After the lithium-extracted solid waste is ball-milled and mixed with anhydrous sodium carbonate, it is calcined at 650°C to 850°C for 1h to 5h for calcination activation treatment to obtain a calcined product; the chemical reaction is as follows: NaAlSi3O8+2Na2CO3=NaAlSiO4+2Na2SiO3+2CO2 SiO2+Na2CO3=Na2SiO3+CO2 S2, calcined product soaking The calcined product in S1 is placed in deionized water for leaching at normal pressure, wherein the mass ratio of water to the calcined product is 5:1-20:1, and leaching solution I is obtained by filtration, which is a water glass solution with extremely low Al impurity content; the calcined product and the leaching solution I are subjected to normal pressure leaching for multiple times according to a liquid-to-solid ratio of 5:1-20:1, and a high-solid content water glass solution and a water leaching filter cake are obtained after filtration; S3, water leaching filter cake acid leaching The water leaching filter cake obtained in S2 is dried, then mixed and stirred with nitric acid, leached, and filtered to obtain leachate II and acid leaching filter cake; the chemical reaction is as follows: Na2SiO3+2HNO3=2NaNO3+H2SiO3 NaAlSiO4+4HNO3=NaNO3+H4SiO4+Al(NO3)3 H4SiO4→H2SiO3+H2O The leachate II is passed through a cation exchange resin to obtain a silica-alumina sol solution.
2. The method according to claim 1, characterized in that The mass ratio of anhydrous sodium carbonate to lithium extraction solid waste in S1 is 0.5-1.5; the lithium extraction solid waste is lithium extraction solid waste with SiO2≥78%, A12O3≤15%, and a crystal phase composition of feldspar and quartz.
3. The method according to claim 1, characterized in that: The temperature of the atmospheric pressure leaching in S2 is 20-95°C, and the leaching time is 30-200 minutes.
4. The method according to claim 1, characterized in that The nitric acid concentration in the S3 is 1-6 mol / L, the ratio of the nitric acid solution to the water leaching filter cake is 5-30 ml / g, and the leaching time is 30-200 min.
5. The method according to claim 1, characterized in that In S3, the acid leached filter cake is mixed with sodium hydroxide and the water glass solution obtained in S2 to obtain an alkali-activated low-carbon gelling material with excellent mechanical properties.
